Medicine, Science, and Making Race in Civil War America - Schwalm, Leslie A. (Leslie Ann), 1956- (Book collections on Project MUSE., 2023)
"Diving deeply into the tables and statistics, specimens, skull collections, reports, questionnaires, and surveys that make up the recently organized and newly available records of the United States Sanitary Commission, Leslie A. Schwalm reveals the racial project of the Civil War as it unfolded in Northern white medical and scientific organizations. Despite the Civil War's importance as a watershed moment in the country's history of anti-Blackness, Union victory and the abolition of slavery did not dislodge the racial hierarchies and ideas about people of African descent that had existed before the war"--